Hubungan Intensitas Menonton Tayangan Kriminal di Sosial Media Terhadap Kenakalan Remaja (Bullying) di Kelas VIII-B MTs. Al-Muhtadi Sendangagung Paciran Tahun 2018 - Virga Septia Nuansa; Ahmad Maujuhan Syah (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2022)
Crime or crime is not a hereditary event (innate from birth, inheritance) nor is it a biological inheritance. Things that encourage someone to commit a crime, namely the inability to adjust economically (maladjustment) and ambitions that are not in accordance with abilities or can be called discrepancies. Modern society which is very complex fosters high material aspirations and is often accompanied by unhealthy social ambitions. For example, when someone wants branded goods such as a capital city artist but is unable to achieve it in a reasonable way, this will encourage someone to commit criminal acts. Criminal acts are actions that violate the rule of law and norms in society. This research was conducted using a qualitative descriptive approach. Bogdan and Taylor define qualitative research as research that produces descriptive data in the form of written or spoken words from people and observable behavior. The results showed that the intensity of watching criminal shows on social media of class VIII-B students had a fairly high ratio or level. Based on research that at least respondents have watched criminal shows at least once a day, when once a day is done continuously, for days, the intensity will change to frequent. Likewise, students' interest in the use of social media.